Nanotechnology Demystified - Linda D Williams (McGraw-Hill "Demystified" series., 2007)
From the Publisher: Learn nanotechnology in a nanosecond. Ever wonder how they make tiny machines? The booming field of nanotechnology is all about building highly advanced super-small machines and devices from the ground up. Nanotechnology Demystified provides you with everything you need to know about the many biological, chemical, physical, environmental, and political aspects of nanotechnology. There's no faster, easier way to enhance your knowledge of this up-and-coming branch of science where little doesn't mean less, it means more: more super-small devices, more jobs, more research opportunities for you. With Nanotechnology Demystified, you can master nanotechnology one simple step at a time-at your own pace. This unique, self-teaching guide features multiple-choice questions at the end of each chapter to pinpoint weaknesses, and a final exam to reinforce what you've learned in the book. This one-of-a-kind, self-teaching text offers: Valuable Nanotech Notes, Tips, Scientific News, and International Trends; Coverage of nanotechnology's influence on pharmaceuticals, biomedical applications, energy, communications, engineering, and the environment; An accessible way to understand topics like carbon nanotubes, quantum dots, nano optics, lab-on-a-chip sensors, nanocomposites, DNA computers, and more. A final exam that you can take and grade yourself. Simple enough for a beginner, but challenging enough for an advanced student, Nanotechnology Demystified is your shortcut to mastering the science of the very smal